(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study examined the effect of the Contributory Pension Administration (CPA) on the post-retirement welfare of retirees in Nigeria, a situational analysis of Benue State University. Survey design was adopted, and the population comprised all 557 retired staff of the institution from 2019 to 2023. Two hypotheses were formulated, and a 5-point Likert questionnaire was administered to 233 retirees of the institution who were selected using the Taro Yamane sample size determination formula. The main instrument of data collection was a document study and a set of questionnaires which was administered to the retirees using snowball sampling technique. The data collected were analyzed with frequency count and percentage while the hypotheses were tested with Pearson correlation coefficient (r) at 0.05 level of significance. The results showed that the contributory pension has not been able to improve the welfare of retirees (p = 0.275, p > 0.05). Also, the correlation is not statistically significant (p = 0.310, p > 0.05), indicating that there is no strong or meaningful relationship between contributory pension administration and the prompt payment of retirement benefits. As such, despite the introduction of the contributory pension scheme, retirees are still confronted with so much hardship that negatively impacts their general well-being and standard of living. The study recommended that: Digitalization of Pension Records, implementation of digital pension records to eliminate bureaucratic bottlenecks and ensure efficient processing of payments. The government should review the contributory pension scheme to increase contributions and ensure sustainability. To avoid negative effects of physical stress, the retirees should plan well for their retirement by investing in other ventures while in the service for a sustainable lifestyle. Retirees should focus on alternative routes of income to supplement retirement benefits.